2020
DOI: 10.3390/ijms21051674
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Aβ42 Peptide Monomers to Sphingomyelin/Cholesterol/Ganglioside Bilayers Assayed by Density Gradient Ultracentrifugation

Abstract: The binding of Aβ42 peptide monomers to sphingomyelin/cholesterol (1:1 mol ratio) bilayers containing 5 mol% gangliosides (either GM1, or GT1b, or a mixture of brain gangliosides) has been assayed by density gradient ultracentrifugation. This procedure provides a direct method for measuring vesicle-bound peptides after non-bound fraction separation. This centrifugation technique has rarely been used in this context previously. The results show that gangliosides increase by about two-fold the amount of Aβ42 bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 42 publications
(68 reference statements)
0
32
0
Order By: Relevance
“…At Aβ/GM1 ratios above ∼0.044, the amyloid conformation was converted to a seed-prone β-structure that recruits monomers from the aqueous phase to form amyloid fibrils different from those formed in solution [ 160 ]. Density gradient ultracentrifugation used for separating the free from the bound peptide enabled Ahyayauch et al to confirm that gangliosides facilitate the binding of Aβ42 to the bilayer and modify the peptide conformation to increase the β-sheet content [ 161 ].…”
Section: Gangliosides and Aβmentioning
confidence: 99%
“…At Aβ/GM1 ratios above ∼0.044, the amyloid conformation was converted to a seed-prone β-structure that recruits monomers from the aqueous phase to form amyloid fibrils different from those formed in solution [ 160 ]. Density gradient ultracentrifugation used for separating the free from the bound peptide enabled Ahyayauch et al to confirm that gangliosides facilitate the binding of Aβ42 to the bilayer and modify the peptide conformation to increase the β-sheet content [ 161 ].…”
Section: Gangliosides and Aβmentioning
confidence: 99%
“…Within this model, the membrane composition is a factor controlling the aggregation process, so a change in membrane composition can shift the ratio between monomeric and aggregated states of Aβ. This hypothesis is further strengthened by the data regarding the contribution of Chol, sphingomyelins, and gangliosides to the neurotoxicity of Aβ aggregates [ 13 , 14 , 15 ], which also highlights these lipids as prime candidates for possible disease defining parameters.…”
Section: Introductionmentioning
confidence: 93%
“…This clearly implies that Aβ monomers have high affinity for GM1‐containing membranes, but not for LUVs in absence of this ganglioside. Also Ahyayauch and colleagues (2020) [38] recently assessed the binding of Aβ 1–42 monomers to LUVs consisting of SM and cholesterol, with and without GM1. The results demonstrated that GM1 doubles the binding of Aβ to GM1‐containing membranes compared to SM:cholesterol vesicles, while it modifies the peptide conformation by increasing its β‐sheet content.…”
Section: Factors Modulating Aβ‐lipid Membrane Interactionsmentioning
confidence: 99%